Regulation of human methylthioadenosine phosphorylase gene by the CBF (CCAAT binding factor)/NF-Y (nuclear factor-Y) - Kadariya, Yuwaraj (Portland Press Ltd., 2005)
hMTAP (human 5′-deoxy-5′-methylthioadenosine phosphorylase) is a key enzyme in the methionine salvage pathway and is frequently inactivated in human tumour cells. To understand the mechanism of the transcriptional regulation of the MTAP gene, we have cloned the 1.29 kb fragment of the hMTAP promoter and identified cis-acting regulatory sequences using a luciferase reporter gene assay. Maximal promoter activity was associated with sequences between −446 and −152, where two CCAAT elements were located. Electrophoretic mobility-shift assay reveals binding of specific complexes at both CCAAT motifs within the MTAP promoter, although more prominent bands were associated with the distal motif (−372 to −368). Supershift experiments and chromatin immunoprecipitation assays indicate that both the proximal and distal complexes bind CBF (CCAAT-binding factor; also known as nuclear factor-Y), and that the distal CCAAT motif has increased levels of CBF binding. We have mapped seven different transcriptional start sites between −135 and −58. Our results show that the hMTAP expression is regulated by a CBF and that the distal one of two CCAAT motifs plays a major role in the transcriptional activation of hMTAP gene.